Simultaneous observation of GNSS scintillation and UHF radar enhanced ion shoulder during EISCAT HF experiment - Sato, Hiroatsu; Yaroshenko, Victoriya; Günzkofer, Florian Ludwig; Varverg, Erik; Rietveld, Michael (2024)
Evolution of artificial field-aligned irregularities (FAIs) is studied by coordinated observations of GNSS satellite and EISCAT UHF radar during EISCAT HF experiments. We show that the electron density variation due to artificial FAIs can be characterized by GNSS scintillation and total electron content (TEC) parameters derived from high-rate GNSS receivers located at EISCAT and in Tromsø when the satellite-receiver links intersected the expected heating impact area around 250 km altitude. GNSS amplitude scintillation and TEC fluctuation data show that the largest density perturbation is found near the magnetic zenith direction. We find that during the existence of small-scale GNSS scintillation, the UHF radar detected an enhanced ion shoulder from a narrow range of altitudes that can lead to erroneous incoherent radar fitting results. In fact, a large deviation is found between the estimated electron densities derived from GNSS TEC and UHF data during this period. We discuss that the source of this particular GNSS scintillation are likely a type of FAIs caused by parametric instabilities.